Short Communication: Molecular identification of Colletotrichum gloeosporioides causing anthracnose on shallot in Bantul, Yogyakarta, Indonesia - LUTHFIANA M. SYAFITRI; ARIF WIBOWO; ANI WIDIASTUTI; SITI SUBANDIYAH; STEPHEN HARPER (Society for Indonesian Biodiversity, 2023)
Abstract. Syafitri LM, Wibowo A, Widiastuti A, Subandiyah S, Harper S. 2023. Short Communication: Molecular identification of Colletotrichum gloeosporioides causing anthracnose on shallot in Bantul, Yogyakarta, Indonesia. Biodiversitas 24: 4530-4534. Anthracnose is one of the most common diseases in shallot cultivation which contributes to cause a significant production loss in Indonesia. Morphological identification of C. gloeosporioides causing anthracnose in Indonesia had been described, however there is no report on the molecular identification to confirm the pathogen species. This report is conducted to reveal species of Colletotrichum causing shallot anthracnose based on specific primer for special complex of Colletotrichum. The method used in this study was sample isolation, morphological observation and molecular identification. The symptomatic leaf sample was collected from Bantul, Yogyakarta, one of Indonesia's shallot productions, to be cultured on potato dextrose agar (PDA) medium. Morphological identification was carried out by using macroscopic and microscopic examinations. Molecular identification of the isolated fungi was amplified using specific primers for Colletotrichum gloeosporioides species complex, CgInt and ITS4. Based on molecular identification, the pathogens were identified as C. gloeosporioides Penz, which showed 98.07% percent identity with C. gloeosporioides AJ311884.1 isolate. This study elucidated that CgInt and ITS4 primers showed as a reliable primer set to be used for Colletotrichum species complex identification. The primer set was able to differ the conserved region among some Colletotrichum spp. Therefore, it is potential to be used for molecular identification. To our best knowledge, this is the first novel report on molecular identification of C. gloeosporioides causing anthracnose in shallot in Indonesia.